On the dynamics of chemical reactions of negative ions - Mikosch, Jochen; Weidemüller, Matthias; Wester, Roland (International reviews in physical chemistry, 2010)
This review discusses the dynamics of negative ion reactions with neutral molecules in the gas phase. Most anion-molecule reactions proceed via a qualitatively different interaction potential than cationic or neutral reactions. It has been and still is the goal of many experiments to understand these reaction dynamics and the different reaction mechanisms they lead to. We will show how rate coefficients and cross-sections for anion-molecule reactions are measured and interpreted to yield information on the underlying dynamics. We will also present more detailed approaches that study either the transient reaction complex or the energy- and angle-resolved scattering of negative ions with neutral molecules. With the help of these different techniques many aspects of anion-molecule reaction dynamics have been unravelled in the last few years. However, we are still far from a complete understanding of the complex molecular interplay that is at work during a negative ion reaction.
Gesehen am 26.04.2023